2013
DOI: 10.1111/bjd.12473
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis, psoriatic arthritis and type 2 diabetes mellitus: a systematic review and meta-analysis

Abstract: Several observational studies have assessed the association between psoriasis, psoriatic arthritis (PsA) and type 2 diabetes mellitus, with inconclusive results. We set out to investigate the association between psoriasis, PsA and type 2 diabetes mellitus. Observational studies assessing the relationship between psoriasis or PsA and type 2 diabetes mellitus up to December 2012 were identified by electronic and hand searches in Medline, Embase, PubMed, the Cochrane Database of Systematic Reviews and Google Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
90
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 57 publications
10
90
1
5
Order By: Relevance
“…2 The economic burden of psoriasis in terms of direct medication costs, physician visits, and indirect costs as a result of productivity costs is also substantial and may exceed over $100 billion annually. 3 Previous studies demonstrated associations between psoriasis and a number of other health comorbidities, including infections, 4,5 diabetes, 6 cardiovascular risk factors and disease, 7 and chronic kidney disease. 8 All of these contribute to disease-related morbidity and may potentially increase hospitalization rates and costs of care.…”
mentioning
confidence: 99%
“…2 The economic burden of psoriasis in terms of direct medication costs, physician visits, and indirect costs as a result of productivity costs is also substantial and may exceed over $100 billion annually. 3 Previous studies demonstrated associations between psoriasis and a number of other health comorbidities, including infections, 4,5 diabetes, 6 cardiovascular risk factors and disease, 7 and chronic kidney disease. 8 All of these contribute to disease-related morbidity and may potentially increase hospitalization rates and costs of care.…”
mentioning
confidence: 99%
“…[1][2][3] The pathophysiology is largely unknown, but it has been hypothesized that systemic inflammation causes reduced insulin sensitivity. 4 Low insulin sensitivity, often referred to as insulin resistance, is an independent risk factor for type 2 diabetes.…”
mentioning
confidence: 99%
“…This fact could be explained by the inflammatory environment promoted by high levels of tumor necrosis factor-alfa and interleukin 6, and hyperinsulinemia, shared by metabolic syndrome, dyslipidemia, type 2 diabetes, and psoriasis, and by the role of angiotensin II, which favors the release of inflammatory cytokines in the case of hypertension. 3,4 In the majority of reports, BMI and weight are considered the main key factors in influencing the treatment response in psoriasis, with a general trend of having a negative effect. 5 However, we did not find significant associations between BMI or weight and biological treatment response.…”
mentioning
confidence: 99%